AUGUSTO DOS ANJOS: A ‘SELF’ IN CONFLICT - Guaraciaba Micheletti; Alessandra Ferreira Ignez (Matraga, 2014)
This paper aims at presenting a stylistic and discursive analysis of three sonnets by Augusto dos Anjos — “A Ideia”, “Psicologia de um vencido” and “Vencedor” — evidencing the ethos of the poetic speaker. It intends to understand the relationship between these poems and the context in which they were written, highlighting the elements of subjectivity, meaning and expressiveness.